Investigating Methods in Teaching Vocabulary to Early Childhood Students - Theo Dedy Palimbunga'; Rosvika Buli; Debby Lestari (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2023)
The mastery of English from an early age is an essential requirement. Kindergarten teachers must equip early childhood studentswith sufficient knowledge and skills in English. It starts with teaching them vocabulary, which facilitates their English communication. However, the main problem often faced is the selection of practical and enjoyable vocabulary teaching methods, as their learning style differs from that of older students. Therefore, this research aimed to investigate processes in teaching vocabulary to early childhood students. This study was conducted at Generation for Christ School using a qualitative descriptive approach. Data were collected through semi-structured interviews involving seven teachers as research informants. The data were analyzed using a qualitative descriptive approach. The results showed that the teaching methods applied by teachers in teaching English vocabulary to early childhood students are movement and songs, Total Physical Response (TPR), games, Grammar Translation Method (GTM), and Communicative Language Teaching (CLT).